Assessment of Clinical Experience of Triple Drug Fixed-dose Combination of Glimepiride, Metformin and Voglibose in the Management of Type 2 Diabetes Mellitus: A Retrospective Study - Ganapathi Bantwal (JCDR Research and Publications Private Limited, 2021)
Introduction: Poor adherence of patients to the polypharmacy approach is a crucial challenge in the management of Type 2 Diabetes Mellitus (T2DM) and use of triple Fixed-Dose Combination (FDC) of metformin, glimepiride, and voglibose is effective in achieving glycaemic control and would aid in improved drug adherence. Aim: To analyse clinical profile and treatment patterns of FDC of glimepiride, metformin, and voglibose with or without other antidiabetic therapy in patients with T2DM. Materials and Methods: A retrospective, observational, multicentric study conducted during August 2019 to March 2020. Included patients of either sex, ≥18 years of age with T2DM and who had received treatment with FDC of glimepiride, metformin, and voglibose of varying strengths with or without other antidiabetic therapy. Data extracted from medical records included demographic characteristics, duration of disease, comorbidities, concomitant medications and dosage pattern. Data were analysed using Chi-square test and Mann-Whitney U test. Results: A total of 2650 patients with T2DM were included, of which 1689 (63.7%) were males. The mean (standard deviation SD) age was 54.2 (11.4) years. The average Body Mass Index (BMI) was 27.2 (4.3) kg/m2 and hypertension 1656 (62.5%) and dyslipidaemia 1109 (41.9%) were the most common co-morbidities. Dipeptidyl peptidase-4 inhibitors 908 (34.3%) and antihypertensives 1601 (60.4%) were the most common concomitant diabetic and non diabetic medications received, respectively. Glimepiride (2 mg)+metformin (500 mg)+voglibose (0.2 mg) FDC twice-a-day 878 (33.1%) was a common triple FDC. A total of 2449 (92.4%) patients were compliant and 2585 (97.9%) achieved glycaemic goal with triple FDC treatment. During the therapy, the majority of patients had decreased weight 1106 (67.2%). The mean Haemoglobin A1c (HbA1c) levels significantly decreased post-treatment (mean change 1.45%; p-value <0.001). Family history of diabetes mellitus, obesity, sedentary lifestyle were the most common risk factors and smoking being prevalent in males. Conclusion: Overall results demonstrate that triple FDC of glimepiride, metformin, and voglibose was effective in reducing HbA1c and weight and was well tolerated. Also, it improves compliance in Indian patients with T2DM.